Digital Transformation in Vendor Management: A Case Study of E-Governance Initiatives in a Public Sector Undertaking - Girish Srivastava (International Journal For Multidisciplinary Research, 2026)
Digitalization of public procurement has become a central plank of governance reform in India, spanning from the Government e-Marketplace (GeM) to organization-specific vendor portals. This paper examines the pace and pattern of digital transformation in the vendor management practices of a large Maharatna public sector undertaking (PSU) in the energy sector. Adopting a descriptive, case-study-based research design built on secondary organizational data, the study maps the case PSU's transition from manual, paper-intensive procurement toward a hybrid digital ecosystem comprising the Government e-Marketplace (GeM), the Government e-Procurement System (GePNIC), a dedicated online Vendor Invoice Management (VIM) portal, digital contract signing, and virtual pre-bid and tender-opening mechanisms. The study finds a marked rise in GeM-routed procurement value for the case PSU, from approximately Rs. 1,033 crore in FY 2020-21 to Rs. 2,541 crore in FY 2022-23, alongside continuing operational friction- vendors are still required to submit several categories of physically notarized and chartered-accountant-attested documents even after digital bid submission, and upload-size ceilings constrain technical-query responses. The paper describes this PSU's vendor management digitalization as a hybrid transition rather than a complete shift, and it proposes measures, including e-attestation integration and unified digital document repositories, to close the residual manual bottleneck. Implications are drawn for other public sector undertakings pursuing vendor-facing digital transformation.